2x-5) = 2(x-5) One Solution Infinitely Many Solutions No Solution 5x + 4) = 5(1-6) 5(x + 4) = 3(x-6) 4x - 2) = 4(x + 2) x + 2(x-5) = 3(x - 2) - 4 b) Intro ✓ Done
![2x5 2x5 One Solution Infinitely Many Solutions No Solution 5x 4 516 5x 4 3x6 4x 2 4x 2 x 2x5 3x 2 4 b Intro Done class=](https://us-static.z-dn.net/files/df3/1faf173fecab936f3a3870a896f3482c.jpg)
9514 1404 393
Answer:
top down: ∞, 0, 1, 0, ∞
Step-by-step explanation:
The equation will have infinite solutions when the left side and right side simplify to the same expression. This is the case for the first and last expressions listed.
2(x -5) = 2(x -5) . . . . expressions are already identical
x +2(x -5) = 3(x -2) -4 ⇒ 3x -10 = 3x -10 . . . the same simplified expression
__
The equation will have no solutions when the x-coefficients are the same, but there are different added constants.
5(x +4) = 5(x -6) ⇒ x +4 = x -6 . . . not true for any x
4(x -2) = 4(x +2) ⇒ x -2 = x +2 . . . not true for any x
__
The equation will have one solution when coefficients of x are different.
5(x +4) = 3(x -6) ⇒ 2x = -38 ⇒ x = -19